2015
DOI: 10.1371/journal.pone.0144930
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of Baculovirus LEF-11 Is Involved in Viral DNA Replication

Abstract: We have previously reported that baculovirus Bombyx mori nucleopolyhedrovirus (BmNPV) late expression factor 11 (lef-11) is associated with viral DNA replication and have demonstrated that it potentially interacts with itself; however, whether LEF-11 forms oligomers and the impact of LEF-11 oligomerization on viral function have not been substantiated. In this study, we first demonstrated that LEF-11 is capable of forming oligomers. Additionally, a series of analyses using BmNPV LEF-11 truncation mutants indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…In the present study, our research revealed that knockdown of ATAD3A, HSPD1 and LEF-11 significantly reduced the protein expression and DNA replication of the virus (Fig. 4)23. This indicated that the ATAD3A and HSPD1 are required for the efficient multiplication of BmNPV.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…In the present study, our research revealed that knockdown of ATAD3A, HSPD1 and LEF-11 significantly reduced the protein expression and DNA replication of the virus (Fig. 4)23. This indicated that the ATAD3A and HSPD1 are required for the efficient multiplication of BmNPV.…”
Section: Discussionsupporting
confidence: 64%
“…Following viral entry of host cells, immediate early gene expression and viral initiation DNA replication occurs2341. After initiating DNA replication of baculovirus, the LEF-11 protein was expressed and hijack host ATPase family members ATAD3A and HSPD139.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations